The Effect of Daylight Illumination in Nursing Buildings on Reading Comfort of Elderly Persons - Yao Fu; Yue Wu; Weijun Gao; Rong Hui (Buildings, 2022)
Reading is one of the popular activities among elderly persons. A reasonable level of daylight illumination can ensure the visual comfort of reading for elderly persons. State arousal level and subjective comfort report are important parameters reflecting the effect of daylight illumination on visual comfort of reading in elderly persons. In this study, daylight illumination measurements were conducted in a nursing institution of Shenyang, China. Moreover, the methods of electrodermal activity (EDA) physiological index measurement and questionnaire scoring were used to compare and analyze the state arousal level and visual comfort of elderly persons under different illumination conditions. The results show that when elderly persons were involved in their daily reading activity, the acceptable daylight illumination range was between 300 and 1000 lx. When the daylight illumination was between 600 and 800 lx, the state arousal level and visual comfort was high; when it was 700 lx, the state arousal level and visual comfort was the highest. Although 500 and 900 lx both indicated neutral illumination, the evaluations were more consistent at 500 lx than at 900 lx. At 300, 400, and 1000 lx, visual comfort was poor and the state arousal level was low. At 300 lx, visual comfort was the worst and the state arousal level was the lowest. This study provides a reliable reference for architects to design the daylight conditions of the living spaces of the elderly.